Green Home Computing For Dummies
It can be easy to be green! Follow these suggestions and help save the planet Get on board the green machine! Here\'s how to assess your technology\'s green factor and make small changes with big impact. You\'ll also find tips for using technology in green ways and advice on getting rid of old devices in an environmentally friendly way. Learn what to buy, when to upgrade, where to find green ideas, and much more. Watch your step Ã¢â,¬â€ calculate the size of your carbon footprint and see how much your electronics contribute to it Do your home work Ã¢â,¬â€ find great advice to help you make the case to your employer for telecommuting options You have the power Ã¢â,¬â€ to use less energy, and you\'ll find lots of ways to do that Green upgrades Ã¢â,¬â€ discover how to give your current computer a green makeover Buying green Ã¢â,¬â€ learn what to look for when shopping for a new computer and peripherals When it\'s time to retire your electronic devices Ã¢â,¬â€ uncover earth-friendly ways to recycle your old computer and be sure you don\'t give away your personal data Sharing is good Ã¢â,¬â€ see how home networks, device sharing, and Windows Home Server can protect the planet The green cloud Ã¢â,¬â€ find out why cloud computing makes green sense Open the book and find: What the Energy Star can tell you Tips for reducing energy use throughout your home The difference between Energy Star and EnergyGuide How to decide what to print and what to read on an electronic device Ten great places to find green hints Definitions of common green terms How to prepare equipment for recycling Guidelines for setting up a green home office